Recurrent duplications of 17q12 associated with variable phenotypes. (30th September 2015) - Mitchell, Elyse; Douglas, Andrew; Kjaegaard, Susanne; Callewaert, Bert; Vanlander, Arnaud; Janssens, Sandra; Yuen, Amy Lawson; Skinner, Cindy; Failla, Pinella; Alberti, Antonino; Avola, Emanuela; Fichera, Marco; et al.
Abstract : The ability to identify the clinical nature of the recurrent duplication of chromosome 17q12 has been limited by its rarity and the diverse range of phenotypes associated with this genomic change. In order to further define the clinical features of affected patients, detailed clinical information was collected in the largest series to date (30 patients and 2 of their siblings) through a multi‐institutional collaborative effort. The majority of patients presented with developmental delays varying from mild to severe. Though dysmorphic features were commonly reported, patients do not have consistent and recognizable features. Cardiac, ophthalmologic, growth, behavioral, and other abnormalities were each present in a subset of patients. The newly associated features potentially resulting from 17q12 duplication include height and weight above the 95th percentile, cataracts, microphthalmia, coloboma, astigmatism, tracheomalacia, cutaneous mosaicism, pectus excavatum, scoliosis, hypermobility, hypospadias, diverticulum of Kommerell, pyloric stenosis, and pseudohypoparathryoidism. The majority of duplications were inherited with some carrier parents reporting learning disabilities or microcephaly. We identified additional, potentially contributory copy number changes in a subset of patients, including one patient each with 16p11.2 deletion and 15q13.3 deletion. Our data further define and expand the clinical spectrum associated with duplications of 17q12 and provide support for the role of genomic modifiers contributing to phenotypic variability. © 2015 Wiley Periodicals, Inc.